First Principles Calculation Guided Material Selection of Poly(propylenemonothiocarbonate) for High-Performance Triboelectric Nanogenerators - Muhammad Naeem Shah; Jiaqi Lu; Dinku Hazarika; Munir Ullah Khan; Srinivasa Rao Pathipati; Kaihang Zhang; Liangquan Xu; Jie Li; Xiaozhi Wang; Shurong Dong; Jikui Luo (Energy Material Advances)
The advancement of the information era has raised growing interest in triboelectric nanogenerators (TENGs) as environmentally friendly micropower sources. However, most developments to increase the power outputs of TENGs have focused on tribo-negative materials, with limited exploration of tribo-positive materials. This research addresses this gap by introducing poly(propylenemonothiocarbonate) (PPMNTC) as a tribo-positive material to enhance TENG performance. Density functional theory was utilized to investigate the triboelectric properties of PPMNTC and compare them with those of polyamide-6 (PA6), a common tribo-positive polymer for TENGs. Density functional theory analysis revealed that PPMNTC exhibits superior electron-donating capabilities due to the existence of high contents of thiol and methoxy groups. Kelvin probe force microscopy was used to confirm the markedly higher surface potential of PPMNTC compared to that of PA6. Meanwhile, cyclic voltammetry measurements revealed that PPMNTC also possesses a deeper highest occupied molecular orbital level than PA6. PPMNTC was utilized to fabricate TENGs paired with fluorinated ethylene propylene film. The 2 × 2 cm2 TENG generated a maximum voltage of 1,450 V and an exceptional transferred charge density of 300 μC/m2, 3- and 4-fold of those of the PA6/fluorinated ethylene propylene TENG, demonstrating the superior properties of PPMNTC as a tribo-positive material. This study drastically expands the material selection for TENGs, offering promising prospects for future applications.